BOTULINUM TOXIN A INJECTION PRECISION CONTROL AT SPASTIC FORMS OF CEREBRAL PALSY: METHODOLOGY CHOICE - O. A. Klochkova; A. L. Kurenkov; A. M. Mamed'yarov; L. S. Namazova-Baranova; A. K. Gevorkyan; Kh. M. Karimova (Union of pediatricians of Russia, 2013)
The article provides general information on botulinum therapy in treating spastic forms of cerebral palsy; a review of modern botulinum toxin A drugs' injection precision control methods at spasticity and other pathologic states is given; advantages and disadvantages of each injection control method are analyzed in detail. Special attention is paid to the substantiated choice of the injection control method in pediatric practice; muscles of the highest degree of complexity for botulinum therapy at spastic forms of cerebral palsy are described. The authors' observations and results of applying ultrasound botulinum toxin A drugs' injection control at different spasticity patterns in children are given.